Fluid inclusion and H–O–S isotope constraints on the genesis of the Ashawayi gold deposit, Southern Tianshan, Xinjiang, NW China - Bo Chen; Hui Chen; Wanli Xing; Yingchao Wang; Yixuan Zhao (Frontiers in Earth Science, 2025)
The Ashawayi gold deposit is situated in the eastern part of the Southern Tianshan Sb–Hg–Au metallogenic belt, a significant source of gold in China. This deposit exhibits typical disseminated mineralization controlled by faults or fractures. This study presents a comprehensive set of petrological, fluid inclusion, and H–O–S isotopic data for the deposit. Fluid inclusions can be classified into three main types, namely, NaCl–H2O, CO2-bearing aqueous solutions, and pure CO2. The quartz from the ore contains fluid inclusions predominantly composed of NaCl–H2O and CO2. The homogenization temperatures of these inclusions range from 200°C to 360°C. Estimates based on fluid inclusion pressures suggest that mineralization occurred at depths of approximately 2–4 km. Mineralization is associated with fault healing and fracturing, which induce secondary fluid immiscibility. Fluid boiling features indicate rapid upwelling of ore fluids from depth, with metal precipitation occurring through decompression at shallower levels. H–O–S isotopes suggest that metals were extracted from the country rock and that the ores were formed through the mixing of metamorphic fluids with meteoric water. A combined analysis classifies the Ashawayi gold deposit as a hypabyssal orogenic gold deposit.